Blood Collection within the Maxillary Sinus following Orbital Fracture Repair: The Impact of Mesh Implants and Drains. Issue 3 (September 2019) - Cox, Jacob T.; Tian, Jing; Merbs, Shannath; Mahoney, Nicholas R.
This article aimed to assess the effects of (1) mesh (e.g., uncoated anatomic titanium plates) versus non-mesh (e.g., porous polyethylene-coated titanium sheets) implant materials and (2) drain placement on the accumulation of blood within the maxillary sinus following surgical repair of orbital floor fractures. Ninety-two patients who received orbital floor fracture repair between 2008 and 2014 were selected, with equal case numbers between categories: (1) non-mesh implant, without drain; (2) non-mesh implant, with drain; (3) mesh implant, without drain; and (4) mesh implant, with drain. Lesion-mapping software was used to measure blood and sinus volumes in postoperative computed tomographic images. Average postoperative maxillary sinus filling was 49% ± 29%. Average sinus filling was similar between mesh and non-mesh implant materials; this was true in cases with a drain (45 vs. 40%, respectively) and without (57 vs. 52%, respectively). Orbital drain placement was associated with a significant reduction ( p = 0.048) in maxillary sinus filling of 12%. Mesh and non-mesh implant materials allow for similar drainage of orbital blood into the maxillary sinus postoperatively. In the majority of cases, space is available within the maxillary sinus to allow for drainage of orbital blood. Intraoperative drain placement is associated with reduced blood pooling within the maxillary sinus, suggesting it allows for drainage of orbital blood to the outside world.